Design, synthesis, biological evaluation and in silico studies of N-(pyridin-2-yl)-benzamides derivatives as quorum sensing inhibitors - Kaur H.; Devi B.; Alajangi H.K.; Kumar R.; Singh G.; Barnwal R.P.; Yadav A.K. (My University, 2025)
The emergence of bacterial resistance against chemical treatment is a big threat to the efficacy of bacterial infection treatment. One of the major reasons for resistance to antimicrobial agents is growth of microorganisms in biofilm. An alternative treatment by developing novel anti-biofilm agents had led to the concept of quorum sensing (QS) inhibition, which primarily targets QS signaling system by disrupting cell-cell communication. Therefore, this study focuses to develop novel antimicrobial agents which work by QS inhibition and act as anti-biofilm agents against Bacillus Subtilis and Pseudomonas Aeruginosa. In this work, a natural product-like scaffolds from Asinex library were screened and N-pyridin-2-yl-benzamide moiety was chosen to design and synthesize. Synthesized compounds were evaluated for potential anti-biofilm activity for the aforesaid microorganisms and also checked for cell viability assay, where two potent compounds 3a and 3c showed their static biofilm activity to ∼59% and ∼58% at 100 μM, respectively against Bacillus subtilis. These synthesized compounds were investigated for physicochemical parameters and binding mode prediction through molecular modelling tools. The interactions and stability of these compounds showed better affinity towards TasA and LasR proteins from Bacillus subtilis and Pseudomonas aeruginosa, respectively. Furthermore, molecular dynamic simulation for 100 ns was executed in order to appreciate the stability of the protein and ligand complex. The overall results promised that N-pyridin-2-yl-benzamide derivatives can be discovered as a lead in developing potent anti-quorum sensing agents against various bacteria. © 2023 Indian Chemical Society